Type of light in sand fly captures (Diptera:Psychodidae) - Jeraldo, Verônica de Lourdes Sierpe; Casanova, Cláudio; Araújo, Edílson Divino de; Cruz, Danilo Esdras Rocha; Pinto, Mara Cristina [UNESP]; Melo, Claudia Moura de (Universidad Nacional de Colombia, 2012)
The number of visceral leishmaniasis cases has been gradually increasing in Brazil. One of the strategies to reduce the disease transmission is based on vector control. It is therefore of great epidemiological importance to develop more refined methods for monitoring and controlling its vectors, which are the phlebotomine sand flies. The present study evaluates the performance of traps using UV light or conventional incandescent, or white, light in sand flies captures. Traps baited with UV light caught higher numbers of sand flies than traps baited with white light, indicating the potential use of UV light, especially in locations of low sand flies densities.

El número de casos de leishmaniasis visceral en Brasil ha ido en aumento, y una de las estrategias para reducir la transmisión de esta enfermedad tiene como base el control de sus vectores. Por tanto, es de gran importancia epidemiológica desarrollar métodos más refinados para monitorear y controlar sus vectores, que son los flebotominos. El presente estudio compara la atracción ejercida por la luz UV en comparación con luz incandescente convencional, o luz blanca, en la captura de flebotominos. Las trampas adaptadas con luz UV capturaron un mayor número de mosquitos que las trampas adaptadas con luz blanca, lo que indica el uso potencial de la luz ultravioleta, especialmente en las localidades de baja densidad de flebotominos.
Tipo de luz en la captura de flebotominos (Diptera: Psychodidae)
Keywords: Lutzomyia longipalpis; Sand flies; UV light; Felbotominos; Luz UV; Lutzomyia longipalpis